Nilai Buddhisme Dalam Tradisi Baritan di Desa Wringinpitu Kecamatan Tegaldlimo Kabupaten Banyuwangi - Mirrah Megha Singamurti; A’an Ari Setepanes (Purwadita : Jurnal Agama dan Budaya, 2022)
The Baritan tradition in Wringinpitu Village, Tegaldlimo District, Banyuwangi Regency is carried out once every long dry season and is carried out in the afternoon. The procession of the Baritan tradition is carried out in mutual cooperation, starting from the preparation, implementation of the tradition, to the closing prayer. There are Buddhist values in the Baritan tradition, namely the value of religious tolerance by the community which is in accordance with the Buddha's sermon in (Udumbarika Sihananda sutta) and King Asoka's Declaration on harmony and mutual respect between religions. The next Buddhist value is found in the prayer that is said by praying for local ancestors. This is in accordance with the Buddhist value, which is found in the Buddha's sermon (Pattakammasutta) which discusses proper blindness according to the advice of the Buddha to relatives, guests, ancestors, kings and the gods.